(untitled) (Journal of the College of Basic Education, 2022)
The pineal gland of male gold capped conure was investigated to find out the description of pineal parts design and cellular components at the light microscopic level by using Haematoxyine – Eosin and periodic acid schift reagent stain methods .The results of morphological aspects revealed that the pineal body (distal part) was broad conical shaped with apex pointing anteriorly and the pineal stalk (proximal part) was narrow long slender and middle structure , which arises from the diencephalon . The result of microscopic examinations indicated that the pineal parenchyma presented a tubule-follicular structural organization. The rudimentary receptor pinealocytes formed a layer of elongated cells with basal nuclei limiting the follicular lumen ,and had sensory cilia projected into the lumen and granular vesicles .These cells were designed as two forms A and B .Three distinct regions of regular stratified organelles distribution was the characteristic feature of the rudimentary receptor pinealocytes form A , while the cells form B were shorter and lacked that polarity in their distribution of internal structures. The secretary pinealocytes located in the external follicular layers were small , round and oval located in the external follicular layers were small , round and oval shaped cells, with numerous dense core vesicles and with irregular shaped nuclei . There were a populations of non pinealocytes , small vessels, capillaries and nerve fibers found in the vascular surfaces.